Microstructure and Mechanical Properties of Friction Stir Welded 2205 Duplex Stainless Steel Butt Joints - Mohamed M. Z. Ahmed (MDPI AG, 2021)
Friction stir welding (FSW) as a solid-state process is an excellent candidate for high softening temperature materials welding; however, extending the tool life is required to make the process cost-effective. This work investigates the use of a high pin to shoulder ratio (65%) tungsten carbide (WC) tool for friction stir welding of 5 mm thick 2205 DSS to extend the tool life of this low-cost tool material. In addition, the effect of FSW parameters in terms of rotational rates, travel speeds, and downward forces on the microstructural features and mechanical properties of the welded joints were investigated. Characterization in terms of visual inspection, macro and microstructures, hardness, and tensile testing was conducted. The obtained results indicated that the combined rotational rate, travel speed, and downward force parameters govern the production of defect-free joints. The 2205 DSS friction stir welds show an enhancement in hardness compared to the base material. The stir zone showed a significantly refined grain structure of ferrite and austenite with the reduction in the average grain size from 8.8 µm and 13.3 µm for the base material to 2.71 µm and 2.24 µm, respectively. Moreover, this joint showed higher yield strength and ultimate tensile strength compared to the DSS as-received material.